Multidisciplinary approach to management of hipofibrinogenemia in pregnancy, a case report - Simeonova Krstevska, Slagjana; Todorovska, Elizabeta; Makarovska Bojadzieva, Tatjana; Petkovic, Elena; Stojcevski, Saso; Samardziski, Igor; Spasovski, Saso; Dejanova, Violeta; Grubovic, Radica; Raka, Florije; Jovanovska, Viktorija; Todorovska, Irena; et al. (Scripta Medica, 2020)
Inherited fibrinogen disorders introduce risk for recurrent abortions, sub-chorionic haematoma, placental abruption and postpartum haemorrhage. This is a case report of a successful pregnancy outcome in a 37-year old woman with hypofibrinogenaemia. She was referred to a coagulation test in the first trimester because of history of preeclampsia and HELLP syndrome in previous pregnancy. Hypofibrinogenaemia was diagnosed with fibrinogen level of 0.7 g/L. During the pregnancy she was regularly monitored for fibrinogen levels and multiple cryoprecipitate concentrates were given. She delivered at 39th gestation week, with elective caesarean section under general anaesthesia. There was one episode of postpartum haemorrhage treated with 2 units of red blood cells, repeated infusions of cryoprecipitate to obtain the level of fibrinogen of 2 g/L. She was discharged on the 6th postpartum day in a good condition. In these disorders levels of fibrinogen should be higher than 1 g/L during pregnancy or 2 g/L in case of caesarean section for successful prenatal and peripartal management.
Keywords: hypofibrinogenaemia; pregnancy; peripartal management